PENGARUH DUKUNGAN REKAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA YAKES TELKOM MAKASSAR - Liza Andriani; Muh. Nur R; Andi Risfan Rizaldi (Jurnal Ilmiah Manajemen Emor (Ekonomi Manajemen Orientasi Riset), 2024)
This research aims to determine the influence of co-worker support and work motivation on employee performance at Yakes Telkom Makassar. This research was conducted using a quantitative approach and data collection techniques through questionnaires. This research uses a non-probability sample, namely a saturated sample, where the entire population is used as a sample, namely 32 respondents at Yakes Telkom Makassar. The analysis technique used in this research is an interactive model with respondents, where the data interpretation is then regulated using data analysis techniques, in this case SPSS. The results of this research show that the variables of co-worker support and work motivation have a positive and significant effect on the performance of Yakes Telkom Makassar employees.